Machine vision technology,standardization,and application in safety industry - Yuan ZHANG; Huifen WANG; Hanming WANG (Dianxin kexue)
The technology and standardization of machine vision were focused on,and the attributes and relations of machine vision,computer vision,and human vision were analyzed.The machine vision related technologies and typical applications such as network information,security intelligent surveillance and intelligent transportation were introduced,as well as the latest development of international and domestic mainstream SDOs of machine vision technology,system and service.The development of the core machine vision technology,video coding for machine vision standards in VCM and DCM,and machine vision systems and application SDOs were elaborated.On this basis,the future development trend of machine vision technology and standardization was analyzed.